Proc. Asia-Pacific Conf. On Semiconducting Silicides and Related Materials 2016 2017
DOI: 10.7567/jjapcp.5.011302
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase synthesis of Mg2Si thin film on sapphire substrate

Abstract: Magnesium silicide (Mg2Si) is expected as a semiconductor material for thermoelectric devices though synthesis of the thin film has been difficult due to difference in thermodynamic properties of Mg and Si. The authors have succeeded in preparing a poly-crystalline Mg2Si thin film with a thickness of ~1m and strong (111) orientation on a sapphire substrate (r plane). The method includes sputter deposition of a Mg/Si bilayer from independent Mg and Si sources and post-annealing (2 h) in argon gas at 900 Pa. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The authors have been devoted to prepare a poly-crystalline Mg 2 Si thin film by annealing a sputter-deposited amorphous Mg/Si bilayer in argon gas atmosphere. In this study, the growth of poly-crystalline Mg 2 Si was identified in the temperature range from 300 ˚C to 400 ˚C [4]. Recently, the authors observed that the Raman peak at 253 cm -1 typical of Mg 2 Si [3] disappeared and the peak at 520 cm -1 typical of poly-Si [5] newly appeared at the temperature higher than 450 ˚C.…”
Section: Introductionmentioning
confidence: 70%
“…The authors have been devoted to prepare a poly-crystalline Mg 2 Si thin film by annealing a sputter-deposited amorphous Mg/Si bilayer in argon gas atmosphere. In this study, the growth of poly-crystalline Mg 2 Si was identified in the temperature range from 300 ˚C to 400 ˚C [4]. Recently, the authors observed that the Raman peak at 253 cm -1 typical of Mg 2 Si [3] disappeared and the peak at 520 cm -1 typical of poly-Si [5] newly appeared at the temperature higher than 450 ˚C.…”
Section: Introductionmentioning
confidence: 70%
“…Various methods have been attempted to grow Mg 2 Si, including sintering and the vertical Bridgman method for bulks, [7][8][9] pulsed laser deposition, molecular beam epitaxy (MBE), and reactive deposition epitaxy for thin films. [10][11][12][13][14][15] Because the performance of optical semiconductor devices is significantly degraded by impurities/defects in the materials, articles describing the relationship between optical device performance and deep-level traps in the device can be easily found. [16][17][18] To date, several devices have been fabricated, and their electrical performances have been reported.…”
Section: Introductionmentioning
confidence: 99%